An exploration of cancer-related mortality attributable to infections in Italy. (30th September 2020) - Ferrara, P; Agüero, F; Conti, S; Masuet-Aumatell, C; Mantovani, L; Ramon-Torrell, J M
Abstract: Background: Previous attempts estimated the impact of infectious agents on cancer incidence in Italy, but the burden of carcinogenic infections on cancer mortality remains unknown. Therefore, we aimed to conduct a preliminary analysis in order to estimate this burden at country level. Methods: We applied the global, regional, or national population attributable fractions for Helicobacter pylori, hepatitis B virus (HBV), hepatitis C virus (HCV), high-risk human papillomavirus (HPV) types, Epstein-Barr virus (EBV), human herpesvirus type 8 (HHV-8), and human T-cell lymphotropic virus type 1 (HTLV-1) - all microorganisms ranked as group 1 carcinogenic agents in human beings by the International Agency for Research on Cancer - to 2015 cancer-related deaths recorded according to the 10th International Classification of Diseases coding system in Italy. Results: We estimated a total of 14, 120 deaths attributable to carcinogenic infections, being 8.3% of the total of cancer-related deaths (n = 170, 339). 58.8% of those occurred in men. H. pylori, HCV, HBC, and HPV accounted for 96.4% of the whole mortality burden attributable to carcinogenic infections in both sexes. H. pylori was responsible for 8, 116 (57.5%) deaths due to gastric carcinoma (non-cardia and non-Hodgkin lymphoma). Hepatitis-related liver cancer accounted for a total 4, 372 deaths: 3, 812 due to HCV infection and 560 to HBV. Cancers related to HPV infection represented the third most frequent cause of deaths due to carcinogenic infections in women. Conclusions: We estimated that one out of 12 cancer deaths in Italy was attributable to an infection sustained by carcinogenic agents. Such mortality burden is potentially avoidable, given that these infections are both potentially preventable and treatable. Thus, these estimates provide actionable metric of the burden for the implementation of specific public health measures. Further analyses will provide more accurate estimates of this disease burden. Key messages: In Italy, one out of 12 cancer-related deaths is attributable to infections sustained by preventable or treatable carcinogenic agents. These estimates provide metric of carcinogenic infections for the implementation of specific public health measures to avert the related mortality burden.